LAYANAN ANTAR JEMPUT SISWA: INOVASI DAN DAMPAKNYA PADA PROSES PEMBELAJARAN DI LEMBAGA PENDIDIKAN ISLAM - M, Yusuf (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2024)
Student shuttle services play a crucial role in supporting effective and efficient learning processes. This article examines the benefits, challenges, and innovations in student shuttle services and their impact on modern education. By integrating advanced technologies such as tracking applications and online reservation systems, these services provide safety, time efficiency, and convenience for students and parents. Additionally, the use of eco-friendly vehicles and learning programs during transit demonstrates the potential of these services in supporting sustainable education. Other innovations include carpooling and the use of electric buses to reduce carbon footprints. However, logistical and cost challenges remain significant obstacles in their implementation. This article offers innovative solutions to address these challenges and provides recommendations for the future development of better student shuttle services. The findings indicate that well-organized shuttle services can enhance students' concentration and academic performance, reduce stress, and positively impact their psychological well-being. Support from the government and community is essential to ensure these services operate optimally and sustainably